Pengaruh Komunikasi, Hubungan Kerja Dan Teamwork Terhadap Kinerja Karyawan Dengan Semangat Kerja Sebagai Variabel Intervening Pada Karyawan PLN Sungai Lansek Kabupaten Sijunjung - Nofritar; Yuliarman Mahmudin (Riset Sinergi Indonesia, 2022)
This study aims to determine how much influence communication, work relations and teamwork have on employee performance with morale as an intervening variable on employees of PLN Sungai Lansek, Sijunjung Regency. Methods of data analysis using a questionnaire, with a sample of 34 respondents. The data analysis methods used are validation and reliability tests, correlation analysis, multiple regression analysis, classical assumption tests, determinants and for hypotheses, the F test and T test are used. Based on the results of the study, it shows that communication, work relations and morale have a positive and significant impact on employee performance. Teamwork has no effect on employee performance and morale. As an Intervening Variable, it can only be used on the working relationship variable. Based on the results of this study, it is expected that the company's management can improve communication and work relations with morale to improve employee performance at PLN Sungai Lansek employees, Sijunjung Regency by going through each indicator